Effects of insertion torque on the structure of dental implants with different connections: Experimental pilot study in vitro. - Sergio Alexandre Gehrke (Public Library of Science (PLoS), 2021)
Objective During the insertion of dental implants in the bone tissue, different torque values can be applied. However, the high applied torque can cause damage to the implant connection. Our study sought to evaluate, by measuring the angle of rotation of the insertion drive and, later microscopic observation, possible changes in the structure of implants of different diameters with 3 different types of connections after the application of 4 different torque intensities. Materials and methods Three hundred tapered dental implants and three hundred insertion drivers were used in the present study. Implants of 3.5 and 4 mm in diameter with 3 connection models were tested: external hexagon (EH), internal hexagon (IH) and Morse taper (MT). Then, sis groups were performed: EH3 group, EH4 group, IH3 group, IH4 group, MT3 group and MT4 group. The samples were submitted to the torque/torsion force at 4 intensities (n = 10 samples per group and intensity): 60, 80, 100 and 120 Ncm. The turning angle of the insertion driver was measured in each test. In addition, in 10 samples from each group, the maximum torque value supported by each implant model was measured. After the tests, all samples were inspected microscopically to describe the observed changes. Results The maximum torque supported by the different implant models showed statistically significant difference (p < 0.0001). The values of the measured angles showed statistically significant differences between the torque values applied within each group (p < 0.001) and between groups with the same torque value (p < 0.001). Conclusions Within the limitations of the present study in vitro, the results showed that high torque values cause mechanical damage to the implants.